Startle Seizures and Diffuse Leukoencephalopathy After Resolution of Herpes Simplex Virus 1 Encephalitis in a Child. (March 2022) - Ng, Andy Cheuk-Him; Kassiri, Janani; Goez, Helly R.; Morneau-Jacob, Francois; Mailo, Janette
We describe a unique clinical presentation of a child after the acute phase of herpes simplex virus 1 (HSV1) encephalitis. A 17-month-old boy first presented with HSV1 encephalitis and was promptly treated with antiviral medication. Seven months later, he was re-admitted for startle seizures. Magnetic Resonance Imaging of the brain showed diffuse confluent leukoencephalopathy. This constellation of symptoms has not been previously reported in HSV1 encephalitis. In conclusion, we showed that brain injury due to HSV1 encephalitis can be associated with the development of startle seizures and diffuse white matter injury in the post-acute phase.